Determinasi Kesenjangan Upah antara Pekerja Penyandang Disabilitas dan Non Disabilitas di Jakarta Tahun 2024 - Rama Fadliansyah; Erika Martha Dinaya; Aulia Rahmatina; Denis Nugroho (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to analyze the determinants of the wage gap between workers with disabilities and non-disabled workers in Jakarta in 2024. The wage gap is understood as the difference in income levels influenced by social, economic, and job-related factors. The research employs a quantitative approach using primary data collected through surveys and interviews with 300 respondents consisting of both workers with disabilities and those without disabilities. Multiple linear regression analysis was applied to identify variables affecting wage levels. The findings reveal a significant difference in the average monthly income between the two groups of workers. Education, work experience, type of occupation, and access to professional training were identified as the key determinants influencing this wage gap. The results also indicate that indirect discrimination remains a challenge in the labor market, where workers with disabilities tend to be concentrated in the informal sector with relatively low wages. This study highlights the importance of inclusive policies and needs-based skills training programs to reduce the wage gap in Jakarta. The findings are expected to serve as a reference for policymakers, educational institutions, and the business sector in promoting fair and equitable employment opportunities.